2021
DOI: 10.1027/0227-5910/a000709
|View full text |Cite
|
Sign up to set email alerts
|

Wiser Reasoning and Less Disgust Have the Potential to Better Achieve Suicide Prevention

Abstract: Abstract. Background: High school and university teachers need to advise students against attempting suicide, the second leading cause of death among 15–29-year-olds. Aims: To investigate the role of reasoning and emotion in advising against suicide. Method: We conducted a study with 130 students at a university that specializes in teachers' education. Participants sat in front of a camera, videotaping their advising against suicide. Three raters scored their transcribed advice on "wise reasoning" (i.e., exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…It is true that facial expressions can provide more detailed explanations to allow for a better understanding of emotions [ 17 , 18 , 19 ], such as anxiety or depression. In a recent study that used facial recognition technology, students who expressed more surprise and less disgust in a suicide advising session were more likely to be receptive to suicide prevention, which showed the relationship between facial expression and potential suicide prevention among students [ 20 ]. Therefore, students’ facial cues are likely to reflect their emotional state, and we propose that these characteristics can be applied to improve the quality of the education system.…”
Section: Introductionmentioning
confidence: 99%
“…It is true that facial expressions can provide more detailed explanations to allow for a better understanding of emotions [ 17 , 18 , 19 ], such as anxiety or depression. In a recent study that used facial recognition technology, students who expressed more surprise and less disgust in a suicide advising session were more likely to be receptive to suicide prevention, which showed the relationship between facial expression and potential suicide prevention among students [ 20 ]. Therefore, students’ facial cues are likely to reflect their emotional state, and we propose that these characteristics can be applied to improve the quality of the education system.…”
Section: Introductionmentioning
confidence: 99%
“…The camera videotaped the participants' frontal-view facial expressions throughout their responses. Previous studies have confirmed the reliability and validity of expression analyses by FaceReader among Chinese participants (Chentsova-Dutton & Tsai, 2010;Hu et al, 2017Hu et al, , 2018Hu et al, , 2021. Following the procedure in previous studies, the "East Asian" face model was used as the training model for this study.…”
Section: Methodsmentioning
confidence: 80%
“…These questions were based on previous studies applying the wise advising paradigm which could evoke real-time authentic emotions behind facial expressions when advising on others' life dilemmas (Hu et al, 2017(Hu et al, , 2018(Hu et al, , 2021. For these questions, participants were told not to speak until they had reflected upon the questions thoroughly and felt ready to begin.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations